1995
DOI: 10.1111/1523-1747.ep12612788
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Regulation of Elastin Synthesis in Human Fibroblasts: Down-Regulation in Fibroblasts from Normal Dermis But Not From Keloids

Abstract: Keloids arise as benign connective tissue masses at sites of injury in genetically predisposed individuals. In addition to excessive collagen accumulation, there is biochemical and histologic evidence of elastic tissue. Previous studies showed that glucocorticoid regulation of collagen synthesis differs in fibroblasts from normal adult dermis and keloids. To define further the abnormal regulation of matrix synthesis in keloid fibroblasts, we examined glucocorticoid regulation of elastin synthesis. The basal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Previous reports on the impact of steroid hormones on ECM synthesis by fibroblasts have shown that testosterone promotes synthesis of collagen in rat coronary artery adventitial fibroblasts (13) and that estrogen inhibits synthesis of collagen in these cells (13) and decreases glycosaminoglycan levels in the uterus of rats (47). Glucocorticoids inhibit the synthesis of collagen (16), elastin (8,9), and glycosaminoglycans (2) in human fibroblasts. The findings were essentially consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on the impact of steroid hormones on ECM synthesis by fibroblasts have shown that testosterone promotes synthesis of collagen in rat coronary artery adventitial fibroblasts (13) and that estrogen inhibits synthesis of collagen in these cells (13) and decreases glycosaminoglycan levels in the uterus of rats (47). Glucocorticoids inhibit the synthesis of collagen (16), elastin (8,9), and glycosaminoglycans (2) in human fibroblasts. The findings were essentially consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts in many regions are targets of steroid hormones including androgen, estrogen, and glucocorticoids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and express receptors for these steroid hormones (3, 11, 18 -22). Fibroblasts exhibit different characteristics depending on the tissue or organ (4) and may have different gene expression programs depending on their anatomic site of origin (23,24).…”
mentioning
confidence: 99%
“…Moreover, keloid formation is one of a group of fibroproliferative diseases characterized by an exaggerated response to injury that occur at higher frequency or with more severe manifestations in people of African ancestry (Smith et al , 2008). We have reported differences in expression of a broad spectrum of wound healing-related genes between normal and keloid fibroblasts under standard culture conditions in medium containing 10% fetal bovine serum (Meyer et al , 2000; Russell et al , 1995; Smith et al , 2008). We have also reported a pattern of differences in growth and synthesis of extracellular matrix induced by several regulators of wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human MAGP-36 is the target protein for Tranilast, a therapeutic drug for hypertrophic scars and keloids (Hiromi Furuichi, personal communication). Hypertrophic scars are known to cause excessive collagen accumulation and deposition of fine immature elastic fibers in the dermis (Russell et al 1995;Roten et al 1996). These findings suggest that MAGP-36 may play an important role in the organization of connective tissue.…”
mentioning
confidence: 97%